An Investigation into Thermal Performance of Mist Water System and The Related Consumption Energy (Journal of Engineering, 2014)
Experimental tests were conducted to investigate the thermal performance (cooling effect) of water mist system consisting of 5μm volume median diameter droplets in reducing the heat gain entering a room through the roof and the west wall by reducing the outside surface temperature due to the evaporative cooling effect during the hot dry summer of Baghdad/Iraq. The test period was Fifty one days during the months May, June, and July 2012. The single test day consists of 16 test hours starting from 8:00 am to 12:00 pm. The results showed a reduction range of 1.71 to 15.5℃ of the roof outside surface temperature and 21.3 to 76.6% reduction in the daily heat flux entering the room through the roof compared with the case of not using water mist system. Also the results show a reduction range of 1.3 to 18.8℃ in the wall outside surface temperature. Finally numerical simulation with ANSYS-FLUENT.14 was conducted to compare its results with the experimental results of the roof and wall tests.